Pengaruh Citra Merek, Potongan Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Di Shine Cake Mulyosari Surabaya - Bunga Shoumizahro; Mohammad Suyanto (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to analyze the effect of brand image, discount and product quality on purchasing decisions at Shine Cake Mulyosari Surabaya. This type of research uses quantitative research with Non-Probability Sampling with Purposive Sampling Technique. The data in this study are primary data obtained from filling out questionnaires through google form with Likert scale calculations. The population is Shine Cake Mulyosari Surabaya consumers who are determined by purposive sampling technique as many as 100 respondents. processing data using SPSS software version 30. The analysis technique used is multiple linear regression analysis to test the hypothesis, while the classic assumption tests used include Normality Test, Multicolonierity Test, and Heteroscedasticity Test. Overall, the indicators used in this study are valid because the correlation coefficient value> 0.195 with a significance level <0.05 and declared reliable because the Cronbach's Alpha coefficient value> 0.60. The classic assumption test results also show that this study has met. The results of this study indicate that Brand Image (X1) has a positive and significant effect on Purchasing Decisions so that H1 is accepted, Discount has a positive and significant effect on Purchasing Decisions so that H2 is accepted, Product Quality has a positive and significant effect on Purchasing Decisions so that H3 is accepted. Brand Image, Discount and Product Quality simultaneously have a positive and significant effect on Purchasing Decisions (Y) so that H4 is accepted.